Innovations In English Teaching: New Technologies For Effective Teaching (Texas Journal of Philology, Culture and History, 2024)
Innovative technologies are new approaches and methods that help make the learning process more interesting, effective and accessible to students. We will look at the advantages of using such technologies, the main innovative methods in teaching English, as well as examples of their application